Characterization of a group unrelated patients with arthrogryposis multiplex congenita - Margarita Valdés-Flores; Leonora Casas-Avila; Edgar Hernández-Zamora; Susana Kofman; Alberto Hidalgo-Bravo (Elsevier, 2016)
ABSTRACT OBJECTIVE: Arthrogryposis multiplex congenita is a relatively rare neuromuscular syndrome, with a prevalence of 1:3000-5000 newborns. In this study, the authors describe the clinical features of a group of 50 unrelated Mexican patients with arthrogryposis multiplex congenita. METHODS: Patients were diagnosed by physical and radiographic examination and the family history was evaluated. RESULTS: Of the 50 cases, nine presented other features (pectum excavatum, cleft palate, mental retardation, ulnar agenesis, etc.). Environmental factors, as well as prenatal and family history, were analyzed. The chromosomal anomalies and clinical entities associated with arthrogryposis multiplex congenita were reported. No chromosomal aberrations were present in the cases with mental retardation. Three unrelated familial cases with arthrogryposis multiplex congenita were observed in which autosomal recessive, autosomal dominant and X-linked inheritance patterns are possible. A literature review regarding arthrogryposis multiplex congenita was also conducted. CONCLUSIONS: It is important to establish patient-specific physical therapy and rehabilitation programs. A multidisciplinary approach is necessary, with medical, surgical, rehabilitation, social and psychological care, including genetic counseling.